Case Studies: Recognition of Prior Learning (RPL) and Skill Deficit: The Role of Open Distance Learning (ODL) - Mamta Srivastava (Commonwealth of Learning, 2015)
Skills acquisition is vital for any economy to compete and grow, particularly in an era of economic and technological change. Skill needs are widespread in most developing countries , including India . Vocational Education and Training (VET) is a direct means of providing workers with skills more relevant to the evolving needs and equitable but must be linked directly to industry needs and requirements. Skilling India may be the biggest challenge facing the country today. Training half a billion people by 2022 is the most ambitious goal ever set by any country in the field of education and training.